Gevrey Regularity of the Global Attractor for Damped Forced KdV Equation on the Real Line (Journal of Mathematical Study, 2018)
We consider here a weakly damped KdV equation on the real line with forcingterm that belongs to some Gevrey space. We prove that the global attractor is alsocontained into such a space of analytic functions.
Keywords: Dissipative KdV equation; global attractor; Gevrey regularity.